HUBUNGAN MOBILISASI DINI DENGAN PENYEMBUHANLUKA POST SECTIO CAESAREA DI RUANG RANAP 2A RS CIBITUNGMEDIKA TAHUN 2023 - Kusuma Atmaja, Ari Wibowo (Jurnal Ayurveda Medistra, 2024)
Background : WHO data in the Global Survey on Maternal and Perinatal Health in 2011 showed that 46.1% of all births were carried out through Sectio Caesarea (SC) (World Health Organization, 2019). The demand for SC in a number of developing countries has increased rapidly every year (Sriyanti, 2016). The incidence of Sectio Caesarea is increasing in developing countries with a percentage of 10-15% for each country. Especially at Cibitung Medika Hospital, it is estimated that there are 70-90 SC patients in one month and there are at least 3-4 patients every day. Research : To find out the Relationship between Early Mobilization and Post Sectio Caesarea Wound Healing in Ranap 2A Room at Cibitung Medika Hospital in 2023 Method :The research method used is analytic. The population in this study were all mothers giving birth with an indication of Sectio Caesarea for the first time at Ranap 2A Cibitung Medika Hospital in Juli-Agustus 2023 with a total sample of 38 people. Result : Based on statistical tests, a p-value of 0.000 was obtained (p <0.05), which means that Ha is accepted and Ho is rejected, meaning that there is a significant relationship between early mobilization and wound healing at Cibitung Medika Hospital in 2023. Early Mobilization, Wound Healing. Key Words : Early mobilization of Wound Healing.